DILATANCY BEHAVIOR IN CONSTANT STRAIN RATE CONSOLIDATION TEST - Berty Sompie; Katsuhiko Arai; Akira Kita (Civil Engineering Dimension, 2006)
Subjected to remolded young clay, this paper shows that a lot of time dependent behavior in the standard consolidation (SC) and constant strain rate consolidation (CSRC) tests is represented systematically by a simple assumption concerning the time dependency of dilatancy. In the SC test, at the first stage of each loading step little dilatancy takes place and dilatancy begins to occur several minutes after step loading. In CSRC test, some time period after the stress state has entered the normally consolidated region, dilatancy tends to occur rapidly with the increase in stress ratio. Since most of dilatancy has taken place at the earlier stage of consolidation, little dilatancy occurs at the latter stage of CSRC process. This tendency makes the specimen stiffer with the passage of time, and makes the vertical pressure and pore pressure increase substantially at the last stage of CSRC process. Consideration to such behavior may be effective to correctly interpret the result of CSRC test.